Clinical and Radiographic Outcomes of Atlanto-Axial Screw Fixation in Neurological Institute of Thailand - Tanawarangkoon, Aiayarch; Tangviriyapaiboon, Teera (Thai Journal of Neurological Surgery, 2025)
Background and Objective: There are many techniques for atlanto-axial fixation such as posterior wiring technique with bone graft fusion, transarticular screwC1-2 fixation, C1 lateral mass with C2 pedicle screw fixation secured by rigid plate or connected by rod system, and modified techniques for C2 screw fixation. The objective of the present study is to compare clinical and radiographic outcomes of patients treated with transarticular screws (TAS) and screw-rod constructs (SRC) for posterior atlantoaxial fusion and subgroup analysis compare clinical and radiographic outcomes of patients treated with translaminar C1 lateral mass screw and sublaminar C1 lateral mass screw of the SRC group. Material and Method: A retrospective charts review were performed using operative database and imaging records to identify all patients who underwent C1-2 screw rod construction or C1-2 transarticular screw fixation between February 2008 and December 2016 at Neurological Institute of Thailand. Fortytwo patients in total were analyzed for clinical and radiographic outcomes. The patients were divided into 2 group: 9 patients in transarticular screw (TAS) fixation and 33 patients in screw rod construct (SRC). In addition, the patients in the SRC group were divided into two groups: 10 patients who were treated with translaminar C1 lateral mass screw and 19 patients who were treated with sublaminar C1 lateral mass screw. Result: Forty-two patients were included in the present study, there are no statistically significant differences were found between the TAS and the SRC groups in ∆ADI [0.82 (-0.29-4.87) VS 0.05 (0- 1.75), P = 0.488], ∆PADI [1.20 (-0.77-4.52) VS 0.05 (0-1.26), P = 0.554], ∆NDAASC [1.85(0.87- 6.16) VS 1.67(0.34-5.20), P = 0.46], ∆NDAASC% [13.45 (5.35-79.59) VS 13.39 (1.89-50.73), P = 0.594], operative time [150 (132.5-347.5) min VS 203 (157-254.5) min, P = 0.453], Blood loss [200 (100-500) ml VS 250 (135-400) ml, P = 0.963] and hospital stay [14 (8.5-24) days VS 10 (6.5-17) days, P = 0.167], postoperative NCSS at 1 year (P = 0.438), the percentage of postoperative NCSS at 1 year (P = 0.419) and postoperative JOA score at 1 year (P = 0.418). In the subgroup analysis of the SRC group, there was no statistically significant difference between the two groups in ∆ADI [0.46 (0-2.91) VS 0.02 (0-0.81), P = 0.454], ∆PADI [0.36 (-0.47-1.57) VS 0.05 (0-0.66), P = 0.947], ∆NDAASC [1.28(0.24-3.92) VS 3.17(0.35-5.63), P = 0.461], ∆NDAASC % [6.57(1.67-30.77) VS 22.43 (1.56-62.98), P = 0.357], postoperative JOA score at 1 year (P = 0.381), postoperative NCSS at 1 year (P = 0.858) and the percentage of postoperative NCSS at 1 year (P = 0.953). Only one patient in the SRC group with sublaminar C1 lateral mass screw technique was found with postoperative occipital neuralgia and 2 patients in the SRC group with sublaminar C1 lateral mass screw technique were found with broken screws. Conclusion: Both TAS and SRC techniques can be used for C1-2 instability since no statistically significant results were found in both group and there was low incidence of complication. Sublaminar and translaminar C1 lateral mass screw techniques showed no statistically significant differences even though sublaminar C1 lateral mass screw technique seems to yield a slightly higher rate of occipital neuralgia. The decision to use either technique of C1-2 fixation must be made after careful review of the individual patient’s anatomy on imaging and the surgeon’s experiences.